Towards an Integrated and Contextualized Research Data Management at the Cluster of Excellence Africa Multiple - Huisl, Jonas; Fichtner, Myriel; Eisenhuth, Philipp; Baumann, Oliver; Schönfeld, Mirco; Jablonski, Stefan; Samimi, Cyrus (Frontiers in African Digital Research : Conference Proceedings, 2022)
In large collaborative, transdisciplinary and potentially geographically distributed research projects, joint data management enables not only the collection of research artifacts; it also fosters discovery and generation of new knowledge in the form of previously invisible interconnections between data. At the same time, a successful system for Research Data Management (RDM) offers immediate benefits to individual researchers: it helps save time finding, sharing, or editing relevant data objects, and can help prevent data loss through centralized backups. Following generations of researchers might benefit from a smartly maintained data collection. Furthermore, funding bodies increasingly require a concept for RDM as part of a grant proposal. As such, a resilient concept for RDM should be considered part of good scientific practice. With these aspects in mind, we present the Digital Research Environment at the Cluster of Excellence Africa Multiple and outline how it can foster best practices for data collection and discovery. Specifically, we introduce WissKI (Wissenschaftliche Kommunikationsinfrastruktur, “scientific communicationinfrastructure”), the system where research data is collected and new interconnections between data items can be determined programmatically.